CENTROID-MOMENT TENSOR SOLUTIONS FOR THE 51-IASPEI SELECTED EARTHQUAKES, 1980-1984 - Ekstrom, G; Dziewonski, A; Woodhouse, J (1987)
The centroid-moment tensor (CMT) technique is applied to the 51 IASPEI selected earthquakes. We use data from the Global Digital Seismograph Network (GDSN), the Regional Seismic Test Network (RSTN) and the International Deployment of Accelerometers (IDA) network. © 1987.